Interventionist versus expectant care for severe pre-eclampsia between 24 and 34 weeks' gestation. - Churchill, David; Duley, Lelia; Thornton, Jim; Jones, Leanne (Wiley, 2013)
Background: Severe pre-eclampsia can cause significant mortality and morbidity for both mother and child, particularly when it occurs remote from term, between 24 and 34 weeks' gestation. The only known cure for this disease is delivery. Some obstetricians advocate early delivery to ensure that the development of serious maternal complications, such as eclampsia (fits) and kidney failure are prevented. Others prefer a more expectant approach delaying delivery in an attempt to reduce the mortality and morbidity for the child associated with being born too early. Objectives: The objective of the review was to compare the effects of a policy of interventionist care and early delivery with a policy of expectant care and delayed delivery for women with early onset severe pre-eclampsia. Search methods: We searched the Cochrane Pregnancy and Childbirth Group's Trials Register (28 February 2013). Selection criteria: Randomised trials comparing the two intervention strategies for women with early onset severe pre-eclampsia. Data collection and analysis: Two review authors independently assessed trials for inclusion, extracted data and assessed risk of bias. Data were checked for accuracy. Main results: Four trials, with a total of 425 women are included in this review. Trials were at low risk of bias for methods of randomisation and allocation concealment; high risk for blinding; unclear risk for incomplete outcome data and other bias; and low risk for selective reporting. There are insufficient data for reliable conclusions about the comparative effects on most outcomes for the mother. For the baby, there is insufficient evidence for reliable conclusions about the effects on stillbirth or death after delivery (risk ratio (RR) 1.08, 95% confidence interval (CI) 0.69 to 1.71; four studies; 425 women). Babies whose mothers had been allocated to the interventionist group had more intraventricular haemorrhage (RR 1.82, 95% CI 1.06 to 3.14; one study; 262 women), more hyaline membrane disease (RR 2.30, 95% CI 1.39 to 3.81; two studies; 133 women), require more ventilation (RR 1.50, 95% CI 1.11 to 2.02; two studies; 300 women) and were more likely to have a lower gestation at birth in days (average mean difference (MD) -9.91, 95% CI -16.37 to -3.45; four studies; 425 women), more likely to be admitted to neonatal intensive care (RR 1.35, 95% CI 1.16 to 1.58) and have a longer stay in the neonatal intensive care unit (average MD 11.14 days, 95% CI 1.57 to 20.72 days; two studies; 125 women) than those allocated an expectant policy. Nevertheless, babies allocated to the interventionist policy were less likely to be small-for-gestational age (RR 0.30, 95% CI 0.14 to 0.65; two studies; 125 women). Women who had been allocated to the interventionist group were more likely to have a caesarean section (RR 1.09, 95% CI 1.01 to 1.18; four studies; 425 women) than those allocated an expectant policy. There were no statistically significant differences between the two strategies for any other outcomes. Authors' conclusions: This review suggests that an expectant approach to the management of women with severe early onset pre-eclampsia may be associated with decreased morbidity for the baby. However, this evidence is based on data from only four trials. Further large trials are needed to confirm or refute these findings and establish if this approach is safe for the mother.